Urgensi Pemahaman Konsep Mahasiswa dalam Pemecahan Masalah ada Pembelajaran Analisis Real Program Studi Pendidikan Matematika - Alianus Zalukhu; Herman Herman; Doni Berkat Tabah Hulu; Nesti Surya Astuti Zebua; Tulus Ikhlas Telaumbanua; Magdalena Susanti Telaumbanua; Ellis Merdiana Panggabean; Dame Ifa Sihombing (Journal on Education, 2023)
This study aims to describe the urgency of understanding student concepts in problem solving in post-graduate real analysis learning in the mathematics education study program at Nias University for the 2022/2023 academic year. This type of research is descriptive qualitative. The research subjects were students of the Mathematics Education Study Program at Nias University for the 2022/2023 academic year. The data collection method used in this study was a survey method, with the instrument used, namely a questionnaire, which was distributed to 40 students of the Mathematics Education Study Program at Nias University for the 2022/2023 academic year. The results of this study indicate the urgency of understanding concepts in overcoming difficulties experienced by students in solving problems in real analysis learning: (1) Difficulties in procedural understanding; (2) difficulties in logical reasoning; (3) difficulty in abstraction; (4) difficulties in formal evidence to solve real problems. Factors that cause students to experience difficulties, namely not understanding the basic concepts of real analysis, students are still confused about abstractions and their relevance in formal evidence to solve real problems.